The Influence of income Expectations, Education, and Access to Capital on Entrepreneurial Interest Before Retirement - Refa Dita Praskagitalokananta; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
etirement is an important phase in life that requires adequate financial resources to achieve prosperity. One alternative is entrepreneurship. Entrepreneurial interest is influenced by several factors including income expectations, education, access to capital, and region. This study aims to analyze the effect of income expectations, education, access to capital, and region on ASN entrepreneurial interest in Surabaya City and Malang Regency. This study uses an associative quantitative approach with primary data obtained from distributing questionnaires at several ASN agencies in Surabaya City and Malang Regency using an accidental sampling technique as many as 171 respondents. Data analysis using cross section data regression processed using e-views and SPSS. The results of data analysis show that the variables of income expectations, access to capital, and region have a significant effect on ASN entrepreneurial interest before retirement in Surabaya City and Malang Regency. Meanwhile, education does not have a significant effect on ASN entrepreneurial interest before retirement in Surabaya City and Malang Regency. In addition, the results of this study also show that ASN in Malang Regency has a higher level of interest in entrepreneurship compared to ASN in Surabaya City.